The Effect Of Training And Work Motivation On Employee Performance With Employee Work Quality As A Indicator Interve Ning Variables At Representative Offices Bank Indonesia North Sumatra Province - Yolanda Saulina Sitorus; Hernawaty (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of Training and Work Motivation on Employee Performance with Employee Work Quality as an intervening variable at the Representative Office of Bank Indonesia, North Sumatra Province. The research employed a quantitative approach using the Structural Equation Modeling (SEM) method based on SmartPLS 3.0. The sample consisted of employees within the Representative Office of Bank Indonesia, North Sumatra Province, selected through purposive sampling. Data were collected using a questionnaire with a 1–5 Likert scale. The results indicate that Work Motivation has a significant effect on Employee Performance and also has a significant effect on Employee Work Quality. Training has a significant effect on Employee Work Quality, but does not directly affect Employee Performance. In addition, Employee Work Quality has been proven to significantly influence Employee Performance. The mediation test results reveal that Employee Work Quality significantly mediates the effect of Work Motivation and Training on Employee Performance. This study emphasizes the importance of improving work quality as a primary strategy to enhance employee performance, particularly through effective training programs and increased work motivation.